2002
DOI: 10.1159/000056058
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Sacrum as an Indicator of a Tethered Spinal Cord

Abstract: The horizontal sacrum has never been described as an indicator of a tethered spinal cord following myelomeningocele closure. We retrospectively analyzed 30 children with a myelomeningocele for this progressive change and its correlation with symptoms. At least two lateral radiographs over time were examined and the lumbosacral angle (LSA) was measured. We found that the majority of these children had an LSA that was greater than would be expected in patients with late and decreased ambulatory abilities. Also, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The posterior shift of the spinal cord was observed to be insufficient in the kyphotically aligned spine after posterior decompression [14]. Lumbar lordosis increases when symptoms worsen in children with lipomyelomeningocele [6][7][8]. Because the lumbar spine usually has a lordosis, and the lordosis increases in tethered cord syndrome patients, the tethered cord can be shifted to the dorsal side in most cases and can be a treatment option.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The posterior shift of the spinal cord was observed to be insufficient in the kyphotically aligned spine after posterior decompression [14]. Lumbar lordosis increases when symptoms worsen in children with lipomyelomeningocele [6][7][8]. Because the lumbar spine usually has a lordosis, and the lordosis increases in tethered cord syndrome patients, the tethered cord can be shifted to the dorsal side in most cases and can be a treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few reports have addressed tethered cord syndrome, almost all of the cases were treated surgically by detethering [1][2][3][4][5][6][7][8][9]. Instead of detethering, we performed surgery to reduce the caudal traction force of the tethered cord by opening the lamina and dural sac and shifting the tethered cord to the dorsal side by harnessing the lumbar lordosis.…”
Section: Introductionmentioning
confidence: 99%
“…9,14 The mechanism underlying the greater propensity to develop a more horizontally positioned sacrum in forms of a tethered spinal cord is speculative, but it is known, for example, that spinal deformities (kyphosis, for example) in children with MMCs who have little function below L-1 develop as a result of the majority of the spinal extensors being rotated ventral to the equator of the spine. 13 Interestingly, a tethered cord in children with MMCs may influence their growth rate 8 and contribute to scoliosis in this group and others. 12 Chernukha et al 3 have commented indirectly on this, stating that an increase in a patient's lordosis may indicate neurological symptoms.…”
Section: Abitbolmentioning
confidence: 91%
“…11,13 This entity is also found in other disease processes such as hypochondroplasia, atelosteogenesis Type II, Weismann-Netter-Stuhl syndrome, and spondylolisthesis. [4][5][6]10 In the present study we review the findings obtained in these two groups of patients, one with an open and one with a closed form of spinal dysraphism.…”
mentioning
confidence: 98%
“…In this regard, Tubbs et al [68] made the interesting observation that the lumbosacral angle (LSA) increases in children with (lipo)myelomeningocele at the time symptoms of TCS deteriorate. They suggested that the LSA as an objective tool may aid the clinician to determine if the spinal cord is symptomatically tethered, and if surgical untethering is needed.…”
Section: Introductionmentioning
confidence: 99%